Can It Happen Again? Using Co‐Produced Theatre to Explore the Challenges Faced by Couples Considering Pregnancy After a De Novo Genetic Diagnosis in a Child - Alison Kay; Anne Goriely; Alexa Gummow; Lisa Hinton; Arti Patel; Marysia Price‐Nowak; Shwetha Ramachandrappa; Jonathon Wells; Francesca Wicks; Minna Jeffery (Health Expectations, 2026)
ABSTRACT Introduction When a couple has a child with a genetic condition, it raises questions when considering future pregnancies. It has typically been considered an easier genetic test result to receive when the condition is de novo (new) in origin, because neither parent is understood to have passed on the genetic change, except in rare cases. However, new scientific research indicates de novo changes are more likely to originate from a single sperm—a risk that increases as fathers age. Research on a personalised recurrence risk assessment strategy is underway (the Impact of PREGCARE study—‘iPREGCARE’). Couples may find this new information on de novo risks from fathers challenging without wider public awareness. This is a reflective case study of using co‐produced theatre to address this need. Methods A range of participants (healthcare practitioners, those with relevant lived experience and the public) were creatively connected through scriptwriting to democratise knowledge production and research communication. Public and Patient Inclusion and Engagement (PPIE) participants were then asked to watch a staged reading of the playscript, to write letters to the characters, and to participate in a post‐performance workshop. Results The staged reading and workshop were attended by 21 people; and over 336 people have viewed the publicly available recording to date. Qualitative analysis of the letters and workshop transcript indicate a major theme of informational discomfort. Two further themes, time pressures and support, focus on what the participants thought was needed but is often compromised or lacking. Conclusion This approach created an opportunity to experiment with the benefits of theatre as a means to share the complicated dilemma couples may face due to new genomic information. Theatre, combined with the opportunity for the audience to write letters to the couple, provided an interactive means of communicating novel research on new reproductive genetic risk information to the public in a tangible and relatable form. Patient or Public Contribution Six co‐production panel members, two additional public contributors and two actors worked with the researchers to develop and deliver the project. A series of meetings and an online collaboration space were used to refine the key messages, approve the script and consider evaluation. The co‐production panel reviewed and suggested edits to the draft journal manuscript.